Teaching mental toughness in tennis - Young, J.; Pearce, A. (Journal of Science and Medicine in Sport, 2010)
It is somewhat incongruous that National Player Development programs place considerable emphasis on developing "mentally tough" tennis players yet there is a general lack of knowledge of how mental toughness can be taught. The aim of this study was to address this void with an examination of former champions` perceptions on teaching mental toughness to aspiring male and female players. Method: As part of a larger study endorsed by the International Tennis Federation, 18 (8 male and 10 female) recently retired top world-ranked Australian tennis players responded to a questionnaire that asked them what recommendations they would make to guide players to be mentally tough and, specifically, what needs to be taught, how and by whom. A series of inductive content analyses was conducted to analyse the qualitative data obtained from participants` responses. Results: Male participants nominated coaches, sport psychologists and former elite players as those best equipped to teach mental toughness to aspiring players. This was consistent with responses from female participants who extended the nominees to also include parents and fitness advisors. The data analyses also revealed that the teaching of mental toughness involved mastering several challenges including those of being self confident and having sound self-awareness skills, a strong work ethic and a balanced perspective on development (versus winning). To address these challenges male participants recommend a range of strategies including the adoption of routines, visualisation, match plans, breathing techniques and rigorous training focused on developing a player's strengths. These strategies were endorsed by female participants who also highlighted the need for those teaching mental toughness to consider emotional (e.g., concern with one's body image) and support group factors. Discussion: The study's findings support that mental toughness is a much sought and desired attribute that, in many instances, differentiates a good player from a "great" player. Participants in the study endorsed the notion that mental toughness can be taught (coached) as well as "caught" (socialised). The main similarity between male and female participants` perspectives highlighted the need for those teaching mental toughness to take an individual approach with the player. This study's value is to provide those entrusted with teaching, or instilling the values inherent in, mental toughness with the conviction, and a range of strategies, that the road to tennis excellence is attainable to players willing to embrace a mentally tough approach to fulfilling their potential.